КОМПЛЕКСНЕ ПОКРАЩЕННЯ ЯКОСТІ ЕЛЕКТРОЕНЕРГІЇ ТА ЗАБЕЗПЕЧЕННЯ ЕЛЕКТРОБЕЗПЕКИ В ЛОКАЛЬНИХ СИСТЕМАХ ЕЛЕКТРОПОСТАЧАННЯ ПРИ ЗАСТОСУВАННІ ГІБРИДНИХ ФІЛЬТРОКОМПЕНСУЮЧИХ ПЕРЕТВОРЮВАЧІВ - Жаркін, А.Ф.; Новський, В.О.; Малахатка, Д.О (Інститут електродинаміки НАН України, Київ, 2018)
The main aspects of the application for the complex improvement of the electrical power quality and the ensure electrical safety in the local power supply systems of the developed hybrid filter compensating converters (GFCC), which are based on a regulated filtering device, "distributive" static synchronous reactive power compensator or a multifunctional reactive power compensator are considered. GFCC are designed to compensate the load currents in the neutral conductor of a three-phase low-voltage network, symmetrical regulation (stabilization) voltage of the load and filtering the currents of higher harmonics in the network. References 14, figures 6, table 1.